The prevalence of obesity and overweight among healthcare workers in Mafikeng Provincial Hospital - Onyebukwa, Chukwuma Victor (Stellenbosch : Stellenbosch University, 2017)
Thesis (MFamMed)--Stellenbosch University, 2011.